2019
DOI: 10.1016/j.celrep.2019.03.043
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Scale CRISPR Screens Identify Human Pluripotency-Specific Genes

Abstract: Highlights d A universal and scalable genetic platform in hPSCs for general use across all lineages d Robust knockout efficiencies translate into high-performance screening at genome scale d Stem cell-specific components of TP53 and OCT4 genetic networks in hPSCs are identified d Validation of PMAIP1 and PAWR function in sensitivity to DNA damage or dissociation

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 73 publications
4
62
0
Order By: Relevance
“…Critically, the DepMap screens were performed using the Avana gRNA library (Doench et al, 2016), indicating that our findings are not specific to our own CRISPR libraries. Similarly, Ihry et al (2019) reported successful genomescale CRISPR screens in a TP53 wild-type human pluripotent stem cell line, despite observing considerable p53-mediated Cas9 toxicity in these cells (Ihry et al, 2018), which is in agreement with data from our own laboratory in a comparable system (Mair et al, 2019). In summary, while the induction of a p53 response in TP53 wildtype cells is not unexpected, it does not hamper the screenability of TP53 wild-type cells in general.…”
supporting
confidence: 84%
“…Critically, the DepMap screens were performed using the Avana gRNA library (Doench et al, 2016), indicating that our findings are not specific to our own CRISPR libraries. Similarly, Ihry et al (2019) reported successful genomescale CRISPR screens in a TP53 wild-type human pluripotent stem cell line, despite observing considerable p53-mediated Cas9 toxicity in these cells (Ihry et al, 2018), which is in agreement with data from our own laboratory in a comparable system (Mair et al, 2019). In summary, while the induction of a p53 response in TP53 wildtype cells is not unexpected, it does not hamper the screenability of TP53 wild-type cells in general.…”
supporting
confidence: 84%
“…One positively selected set is related to the p53 pathway ("TP53 Network"), which is expected, as it is known that disabling p53-mediated DNA repair signaling increases proliferation in iPSCs (Haapaniemi et al 2018;Ihry et al 2018) . Several of the genes positively selected in iPSCs upon perturbation (PMAIP1, TP53, CHECK2) were recently individually confirmed in independent studies of stem cell specific essential genes Ihry et al 2019) .…”
Section: Double Grna Library Enables Screens In Ipscsmentioning
confidence: 88%
“…Our method may offer a route to find the best gene modulations (overexpression or partial knockdown) to carry out on multiple genes and towards multiple cellular objectives. For instance, expression vectors found with our method can be potentially used as a guide for CRISPR-Cas or CombiGEM systems [66], which have already proven successful in editing and modulating expression simultaneously across the genome [67], [68], e.g. to prioritize therapeutic targets in cancer cells [69].…”
Section: Discussionmentioning
confidence: 99%